Pelayanan Teknologi Informasi Manajemen: Peran, Tanggung Jawab, dan Pengukuran - Muhammad Prima Aji; Muhammad Irwan Padli Nasution (Getpress Management Journals, 2025)
The development of information technology has brought significant changes to how organizations manage and evaluate their performance. Data management technologies such as management information systems, big data analytics, and artificial intelligence (AI) have become strategic tools for supporting data-driven decision-making processes. This article aims to examine the role of data management technology in measuring organizational performance effectively and efficiently. Through a descriptive qualitative approach using literature studies, the research finds that the implementation of data management technology not only improves the accuracy of performance measurement but also accelerates the analysis process and enhances organizational transparency. The results indicate that organizations utilizing data-driven technologies are able to establish performance measurement systems that are more adaptive to changes in the business environment.